Tinjauan Yuridis atas Tindak Pidana Pencemaran Nama Baik Terhadap Institusi Negara - I Nyoman Surya Natha; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Defamation often occurs in the real world and online. Basically the law on defamation has been regulated and formulated in Article 310 of the Criminal Code which consists of 3 (three) paragraphs. It is contained in Article 27 paragraph (3) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). However, in this case, it is necessary to hold strict sanctions in order to overcome defamation of state institutions or institutions. The purpose of this research is to reveal the application of law to the Criminal Acts of Blasphemy against State institutions and the judge's legal considerations on Decision Number 117/Pid.Sus /2020/PN Kka. This research is a normative research with legislation approach. The sources of legal materials used are primary, secondary and tertiary sources of legal materials. The technique of collecting legal materials is done by studying literature which is then analyzed systematically. The results of the study revealed that the judge's legal considerations against Decision Number 117/Pid.Sus/2020/PN Kka which stated that the Defendant Sumarni Alias ​​Arni Binti Daso was legally and convincingly proven guilty of committing a criminal act intentionally and without the right to transmit and/or make it accessible. electronic information that contains defamation, as regulated and threatened with criminality in Article 45 paragraph (3) of the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions in the Indictment Sole Prosecutor.